2022
DOI: 10.3390/ani12111452
|View full text |Cite
|
Sign up to set email alerts
|

Nose-Flap Devices Used for Two-Stage Weaning Produce Wounds in the Nostrils of Beef Calves: Case Report

Abstract: This case report aims to describe the occurrence of negative impacts of wearing nose-flap devices on beef calves subjected to the two-stage weaning method. Forty-one calves, twenty-one pure Nellore and twenty F1 Angus-Nellore, were weaned on average at 236 days of age. Commercial nose-flap devices were fitted in the nostrils of the calves (d0) to prevent suckling and removed five days later (d5). Individual body weights were assessed at d0 and d5, and average daily gain (ADG) was calculated. At d5, during nose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…The closest information in terms of the functional aspects of attachment to the nasal septum is how many flaps were lost before removal. While Haley et al (2005) and Taylor et al (2020) both reported less than 5% flap loss, others have reported 24% ( Lambertz et al, 2015 ) or even 27% ( Valente et al, 2022 ) loss of the flap before calves had them manually removed. At the time of the current study, nose flap loss has not been evaluated in relationship to calf size or nostril septum width measurement.…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…The closest information in terms of the functional aspects of attachment to the nasal septum is how many flaps were lost before removal. While Haley et al (2005) and Taylor et al (2020) both reported less than 5% flap loss, others have reported 24% ( Lambertz et al, 2015 ) or even 27% ( Valente et al, 2022 ) loss of the flap before calves had them manually removed. At the time of the current study, nose flap loss has not been evaluated in relationship to calf size or nostril septum width measurement.…”
Section: Introductionmentioning
confidence: 91%
“…When compared to abrupt weaning, calf weight gain was not affected by the nose flap ( Burke et al, 2009 ; Lambertz et al, 2015 ; Alvez et al, 2016 ). Some researchers have reported that calves had a decrease in daily weight gain when the nose flap was in place, but similar overall gains compared to abruptly weaned calves ( Haley et al, 2005 ; Burke et al, 2009 ; Valente et al, 2022 ). Plasma cortisol concentrations remained in normal range 0.3 μg/dL ( Hopster et al, 1999 ) to 5.5 μg/dL ( Doornenbal et al, 1988 ) for calves that were weaned with a nose flap ( Freeman et al, 2021 ) suggesting that this method did not cause additional stress to the calves.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations